Um estudo sobre métodos de integração direta para a análise dinâmica não-linear de estruturas - Leal-Toledo, Regina Célia Paula (1983)
ln this work we study numerical aspects of direct integration algorithms for non-linear dynamic analysis by the Finite Element Method. Included here are the Newmark Method, the Central Difference Method and also the treatment of the non-linear terms as pseudo-forces. Some criteria based on energy conservation concepts which are used to check both the dynamic equilibrium and algorithm stability are examined and compared with criteria usually employed. Numerical results are presented and discussed in order to provide practical guidelines to the analysis of engineering problems.